Pest status of bean stem maggot (ophiomyia spp.) and black bean aphid (aphis fabae) in taita district, Kenya - Ochilo, W; Nyamasyo, GH (2011)
On-station and on-farm studies were carried out in 2008 during the long rains (March – May), in Taita region, Kenya, to assess the effect of various soil fertility regimens on bean stem maggot (BSM) (Ophiomyia spp.) and black bean aphid (BBA) (Aphis fabae) incidences. These studies aimed at gathering information useful in the development of an IPM programme for the project on conservation and sustainable management of below-ground biodiversity (CSM-BGBD). The incidences of bean stem maggot and black bean aphid were significantly (p = 0.05) higher at the less fertile environment than at the relatively more fertile environment. Additionally, application of Mavuno + Trichoderma and Trichoderma reduced bean stem maggot incidence. ISFM interventions had no effect on BBA incidence. Instead, variation in black bean aphid incidence depended mainly on location; with locations characterised by low rainfall and high temperatures having a higher incidence of black bean aphid than those locations characterised by relatively high rainfall and low temperatures.